2017
DOI: 10.18632/oncotarget.19311
|View full text |Cite
|
Sign up to set email alerts
|

Von Hippel-Lindau regulates interleukin-32β stability in ovarian cancer cells

Abstract: Hypoxia-induced interleukin-32β (IL-32β) shifts the metabolic program to the enhanced glycolytic pathway. In the present study, the underlying mechanism by which hypoxia-induced IL-32β stability is regulated was investigated in ovarian cancer cells. IL-32β expression increased under hypoxic conditions in ovarian cancer cells as it did in breast cancer cells. The amount of IL-32β was regulated by post-translational control rather than by transcriptional activation. Under normoxic conditions, IL-32β was continuo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…IL-32 is also induced during oxidative stress. 24,[77][78][79] In malignant plasma cells, the increase of IL-32 in response to hypoxia was dependent on hypoxia inducible factor 1-alpha (HIF1 ). 24 In ovarian cancer cells, hypoxia-induced reactive oxygen species (ROS) promoted accumulation of IL-32 .…”
Section: Oxidative Stressmentioning
confidence: 99%
See 2 more Smart Citations
“…IL-32 is also induced during oxidative stress. 24,[77][78][79] In malignant plasma cells, the increase of IL-32 in response to hypoxia was dependent on hypoxia inducible factor 1-alpha (HIF1 ). 24 In ovarian cancer cells, hypoxia-induced reactive oxygen species (ROS) promoted accumulation of IL-32 .…”
Section: Oxidative Stressmentioning
confidence: 99%
“…Others have showed that in ovarian cancer cells IL‐32β stability is directly regulated by von‐Hippel Lindau (VHL) E3 ligase and that hypoxia‐induced ROS promoted accumulation of IL‐32β. IL‐32β formed a trimeric complex with VHL and PKCδ in normal oxygen levels resulting in a continuous degradation of IL‐32, and when stabilized by hypoxia, IL‐32 prevented PKCδ from inducing oxidative stress‐induced apoptosis 78 . Finally, IL‐32θ could bind PKCδ and STAT3 in PMA‐stimulated THP‐1 cells, phosphorylating STAT3 at the Ser727.…”
Section: Il‐32 Receptor(s) and Binding Partnersmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, hypoxia-induced IL-32β interacts with protein kinase C δ (PKCδ) and this interaction results in the suppression of PKCδ-induced apoptosis (52). We also showed that the accumulated IL-32β translocates to the mitochondria under hypoxic conditions.…”
Section: Role Of Il-32 In Other Types Of Cancermentioning
confidence: 99%
“…MAVS and KLF4 are VHL substrates, but whether these regulations are dependent on oxygen availability is unknown [ 63 , 68 ]. The oxygen/VHL-mediated ubiquitination and proteasome degradation of proteins involve EGFR, atypical protein kinase C, Sprouty 2, β-adrenergic receptor II, Myb-binding protein 160, RPB1, RPB7, Cep68, Interleulin-32β, CERKL, FLNA, and ERK5/BMK1 [ 64 , 65 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 ]. In addition, VHL transcriptionally regulates aldehyde dehydrogenase 2 ( ALDH2 ) through the direct activation of transcription factor HNF-4α in an HIF- and VHL E3 ligase-independent fashion, which contributes to the sensitivity of ccRCC cells to anthracycline treatment [ 80 ].…”
Section: Other Vhl Downstream Regulatorsmentioning
confidence: 99%